Effect of Vemurafenib on the Pharmacokinetics of a Single Dose of Digoxin in Patients With BRAFV600 Mutation–Positive Metastatic Malignancy. (12th April 2018) - Zhang, Weijiang; McIntyre, Christine; Kuhn, Melissa; Forbes, Harper; Kim, Tae Min; Lee, Jeeyun; Demidov, Lev; Colburn, Dawn
Abstract: The primary objective of this phase 1, open‐label, multicenter, 3‐period, fixed‐sequence study was to evaluate the effect of multiple doses of vemurafenib on the pharmacokinetics of a single dose of digoxin, a probe P‐glycoprotein (P‐gp) substrate, in patients with BRAF V600 mutation‐positive metastatic malignancy. Following a 28‐day screening period, patients received a single oral dose of digoxin 0.25 mg on day 1 in period A, oral vemurafenib 960 mg twice daily for 21 days in period B (days 8‐28), and a single oral dose of digoxin 0.25 mg on day 29 and vemurafenib 960 mg twice a day for 7 days (days 29‐35) in period C. Log‐transformed area under the concentration‐time curve and peak concentration values for digoxin were compared between periods A (digoxin alone) and C (digoxin + vemurafenib) using an analysis of variance model. Twenty‐six patients were evaluated for the primary pharmacokinetic analysis. The geometric mean ratio (period C/period A) of area under the curve to the last measurable concentration for digoxin was 1.82 (90%CI 1.63 to 2.02), and the geometric mean ratio of peak concentrations was 1.47 (90%CI 1.30 to 1.65); the 90%CIs were outside of the equivalence limits of 0.82 to 1.22, indicating an effect of vemurafenib on digoxin. Multiple oral doses of vemurafenib were generally well tolerated, with an adverse event profile similar to that previously seen in phase 2 and 3 studies of vemurafenib monotherapy. This study confirmed vemurafenib as an inhibitor of P‐gp in vivo with a statistically significant drug‐drug interaction with digoxin. Caution should be exercised when dosing vemurafenib concurrently with P‐gp substrates.